A scanning electron microscopy study of projectile entry fractures in cortical bone; genesis and microarchitectural features - Rickman, John M.; Painter, Jonathan; Hazael, Rachael (Springer, 2021)
The present paper presents a scanning electron microscope (SEM) analysis of the genesis and microarchitecture of experimentally induced cortical entry fractures in porcine scapulae impacted at velocities ranging from 54 to 897 m/s. SEM observation was conducted on polyurethane replicas cast from negative silicone moulds. Analysis of the sequence of fracture processes operative during projectile impact revealed the presence of ring cracks at the site of impact, confirming that penetration in sandwich bones is achieved by cone crack propagation. Despite impulsive loading, two forms of plastic deformation were identified in the cortical bone surrounding the entry fracture up to a maximum velocity of 871 m/s. Microscopic radial and concentric cracks were associated with projectile impact, and the role of pores and pits as stress concentrators was captured. Possible underlying mechanisms for the observed plastic deformation are described, and the diagnostic utility of SEM analysis is presented.
Keywords: Forensic anthropology; Projectile trauma; Ring cracking; Cone cracking; Plastic deformation; Shock waves; Hydroxyapatite crystals